Awareness of Occupational Health and Safety Guarantees for Workers at Dompet Dhuafa Jakarta - K, Raissya H Dianies (GoResearch - Research & Publishing House, 2025)
Occupational accidents and work-related illnesses remain a serious challenge in Indonesia, including in the philanthropic sector such as Dompet Dhuafa Jakarta, which plays a vital role in social services. This study aims to analyze the level of worker awareness regarding occupational health and safety (OHS) guarantees and to identify factors influencing the implementation of the Occupational Health and Safety Management System (SMK3) within the organization. A descriptive qualitative method was employed, using in-depth interviews, observations, and document reviews. The findings indicate that Dompet Dhuafa Jakarta has demonstrated initial commitment to OHS implementation through training, emergency response simulations, and collaboration with the Social Security Administration Agency (BPJS Ketenagakerjaan). However, the implementation still faces several challenges, including unintegrated policies, limite d internal supervision, insufficient human resources, and the absence of a systematic evaluation framework. This research recommends strengthening all elements of SMK3, enhancing OHS human resource capacity, and developing a technology-based reporting and risk monitoring system. These findings are expected to provide strategic guidance for Dompet Dhuafa and other philanthropic institutions in establishing safe, healthy, and sustainable work environments.